Protecting what's mine - Score, Lucy (Naperville, IL : Bloom Books, 2022)
"Fire Chief Lincoln Reed is known for his heroics in the fire department and in the bedroom. Life is a never-ending good time. Until Mackenzie O'Neil lands in the middle of the accident scene he's working ... and then his backyard. Too bad she's immune to flirty first responders. Flight trauma surgeon Mackenzie O'Neil is on a crash course with burnout. She's got a scar on her face and shake in her hands. A temporary job as a small-town family physician is just the prescription. She'll learn to meditate. Sleep more. Take up gardening. She definitely won't take her shirtless, firefighting neighbor's hot body for a test drive. But Linc and his tattoos are very persuasive. What's a harmless little adrenaline-fueled fling between neighbors? It's all naked fun and games until the shadows from Mack's past find their way into her present. Can Linc be her hero when she needs him the most or will their scars ruin everything? One thing is certain: Someone is going to get burned"--
Keywords: Man-woman relationships -- Fiction; Fire chiefs -- Fiction; Women surgeons -- Fiction; Small cities -- Fiction; Romance fiction; Novels